2011
DOI: 10.1108/09600031111147817
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal cooperations between logistics service providers: motives, structure, performance

Abstract: Purpose-This paper aims to provide a comprehensive overview of the motives, structure and performance attributes of horizontal cooperations between logistics service providers (LSPs). Based on an analytical classification model, distinctive types of logistics cooperation that characterize the logistics landscape are identified. Design/methodology/approach-Empirical data were collected on horizontal LSP cooperations from managers of German LSPs. Different uni-and multi-variate statistical methods including ANOV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
129
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(134 citation statements)
references
References 79 publications
(134 reference statements)
3
129
1
1
Order By: Relevance
“…The subject of retail intermodal logistics includes the retailers themselves as well as rail operators and third-party logistics providers (3PLs). Schmoltzi & Wallenburg (2011) found that while almost 60% of 3PLs in their study operated at least one horizontal partnership with other 3PLs, the failure rate was below 19%, against an average failure rate for horizontal collaborations in many industries ranging from 50% to 70%. The authors also found that, while horizontal collaboration might be thought to be based on cost reduction, the primary motivations revealed in their study were service quality improvement and market share enhancement.…”
Section: Retail Logistics In the Ukmentioning
confidence: 84%
“…The subject of retail intermodal logistics includes the retailers themselves as well as rail operators and third-party logistics providers (3PLs). Schmoltzi & Wallenburg (2011) found that while almost 60% of 3PLs in their study operated at least one horizontal partnership with other 3PLs, the failure rate was below 19%, against an average failure rate for horizontal collaborations in many industries ranging from 50% to 70%. The authors also found that, while horizontal collaboration might be thought to be based on cost reduction, the primary motivations revealed in their study were service quality improvement and market share enhancement.…”
Section: Retail Logistics In the Ukmentioning
confidence: 84%
“…Inter-organizational relationships, where parties with different corporate cultures, different regions, different mindsets, and different ways of doing things interact intensively, provide fertile ground for such conflicts [18,29]-a situation typical for horizontal LSP alliances [3]. Further factors that create tension and almost inevitably lead to conflicts are mutual dependencies that require continuous interactions [30], different viewpoints concerning temporal aspects (i.e., short-term vs. long-term) [31], diverging goals, and, in the specific case of horizontal cooperation, competitive tension [31,32] among members.…”
Section: Conflict Types and Their Outcomesmentioning
confidence: 99%
“…Compared to vertical relationships, the mode of collaboration in horizontal alliances differs due to their often multilateral setup [3]. This complicates collaborative processes as more than two companies are to be included.…”
Section: Limitations and Further Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Cai et al (2009) Todeva & Knoke (2005) developed a 13-stage model of cooperation structure capturing the spectrum from market/contract to hierarchy/integration: market relations, action sets, industry standard groups, subcontractor networks, licensing, franchising, cartels, strategic cooperative agreements, R&D consortia, cooperatives, equity investments, joint ventures, hierarchical relations. Schmoltzi & Wallenburg (2011) condensed these hybrid types (and other previous work by Parkhe, 1991;Dussauge & Garrette, 1997;Klint & Sjöberg, 2003) into four: verbal agreements, written contracts without equity involvement, minority stake agreements, joint venture agreements. Thus the key element in that formulation is the level of the financial stake taken by the partners.…”
Section: Governance Forms For Supply Chain Collaboration and Integrationmentioning
confidence: 99%